2012
DOI: 10.1371/journal.pone.0029802
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Rejection Pathology after Orthotopic Lung Transplantation in Mice: The Development of a Murine BOS Model and Its Drawbacks

Abstract: Almost all animal models for chronic rejection (CR) after lung transplantation (LTx) fail to resemble the human situation. It was our attempt to develop a representative model of CR in mice. Orthotopic LTx was performed in allografts receiving daily immunosuppression with steroids and cyclosporine. Controls included isografts and mice only undergoing thoracotomy (SHAM). Allografts were sacrificed 2, 4, 6, 8, 10 or 12 weeks after LTx. Pulmonary function was measured repeatedly in the 12w allografts, isografts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 22 publications
(23 reference statements)
1
23
1
Order By: Relevance
“…In contrast, a recent study in this model showed obliterative airway lesions in minor histocompatibility mismatched transplants that were significantly reduced after neutralization of IL-17A (8). Also notable was a recent report of similar airway lesions in fully MHC-mismatched transplants treated with conventional immunosuppression, including cyclosporine A and corticosteroids, although cytokine responses were not evaluated in this study (9). Although IFN-g-mediated type 1 responses have been demonstrated in ACR in multiple experimental transplant models, including the mouse orthotopic lung transplant model, these responses have also been shown to be dispensable for rejection.…”
Section: Clinical Relevancecontrasting
confidence: 74%
See 2 more Smart Citations
“…In contrast, a recent study in this model showed obliterative airway lesions in minor histocompatibility mismatched transplants that were significantly reduced after neutralization of IL-17A (8). Also notable was a recent report of similar airway lesions in fully MHC-mismatched transplants treated with conventional immunosuppression, including cyclosporine A and corticosteroids, although cytokine responses were not evaluated in this study (9). Although IFN-g-mediated type 1 responses have been demonstrated in ACR in multiple experimental transplant models, including the mouse orthotopic lung transplant model, these responses have also been shown to be dispensable for rejection.…”
Section: Clinical Relevancecontrasting
confidence: 74%
“…Therefore, this molecular state could be relevant to the clinical field of lung transplant. In fact, a recent study showed the development of OB lesions in mouse recipients of orthotopic lung transplant that were treated with calcineurin inhibitors and steroids, whereas these lesions have not been previously described in the untreated, fully MHC-mismatched mouse model (9), suggesting a possible role of immunosuppression effects in the development of these lesions. Moreover, we believe that understanding the downstream, pathologic effects of the CD8 (36).…”
Section: Cd8mentioning
confidence: 93%
See 1 more Smart Citation
“…Although mouse orthotopic lung transplant models are increasingly used, the consistency of reproducing BOS and chronic rejection is concerning (38,39). To improve the tracheal transplant model to better recapitulate the human setting of OB, we adapted the traditional subcutaneous approach by conducting IPTT, which places the allograft into a pulmonary milieu.…”
Section: Discussionmentioning
confidence: 99%
“…However, these airway fibrotic lesions were noted in only 50% of the transplanted mice and were limited to a small number of airways in the allografts. Use of immunosuppression (cyclosporine + steroids) to prolong graft life in MHC mismatch (BALB/c→C57BL/6) has also allowed for investigation of the development of OB pathology (119). This model only generates OB-like lesions in 25%-50% of the mice, with many mice demonstrating no evidence of OB or regaining normal histology after 12 weeks.…”
Section: Cladmentioning
confidence: 99%